THE EFFECTIVENESS OF ANIMATED VIDEO AND PICTURE STORIES ON CHILDRENS KNOWLEGE OF SEX EDUCATION IN PREVENTING SEXUAL VIOLENCE - Idfi Widi Lestari; oon fatonah akbarini; Tessa Siswina; Dini Fitri Damayanti; Dianna Dianna (Poltekkes Kemenkes Pontianak, 2026)
Background: Child sexual violence has become a major public health and social concern worldwide and in Indonesia, highlighting the urgent need for effective preventive educational interventions. According to the Indonesian Ministry of Women's Empowerment and Child Protection, 31,947 cases of violence were reported in 2024. Purpose: To analyze the effectiveness of animated videos and illustrated stories on children's sex education knowledge in sexual violence prevention efforts. Methods: This research is a quasi-experimental study with a pretest-posttest without control group design. Sampling technique utilized cluster random sampling with a total of 46 respondents. Results: Knowledge scores increased significantly in both the animated video group (75.30 ± 16.49 to 89.00 ± 8.44; p < 0.001) and the illustrated story group (76.22 ± 13.05 to 91.61 ± 9.70; p < 0.001). No statistically significant difference was found between the two educational media (p = 0.772). Conclusion: Animated videos and illustrated stories are effective and can be used as health education media in children's sexual education. There is no significant difference in the effectiveness of animated video and illustrated story media on sex education knowledge in sexual violence prevention efforts.